TINGKAT AKULTURASI BUDAYA SUKU TERHADAP PENDALAMAN NILAI-NILAI MORAL MASYARAKAT MUSLIM MULTIKULTURAL KOTA PALU - DEWI SATRIA AHMAR; MUHAMMAD FATH AZZAJJAD; MUSNAJAM MUSNAJAM (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
This study aims to examine the level of cultural acculturation among various ethnic groups in Palu City in relation to the deepening of Islamic moral values within a multicultural Muslim society. The main focus is to understand how interethnic cultural interactions influence the integration of Islamic moral values in both family and community life. The research employs a descriptive quantitative approach using survey techniques through questionnaires distributed to residents from five dominant ethnic groups: Kaili, Makassar-Bugis, Javanese, Gorontalo, and Minangkabau. Data were analyzed using descriptive statistical techniques and visualized through bar chart mapping. The findings reveal that the Kaili ethnic group demonstrates the highest level of cultural acculturation and Islamic moral values, particularly in cultural interaction (90%) and integration of Islamic values (88%). The Gorontalo ethnic group recorded the lowest scores, possibly due to a strong attachment to their native culture. A positive correlation was identified between cultural acculturation and the internalization of Islamic moral values. In conclusion, the greater the degree of acculturation with the locally Islamized culture, the deeper the integration of Islamic moral values in social life. This research underscores the importance of a multicultural approach in fostering a harmonious and morally grounded Muslim community.